Hydration profile and sweat loss perception of male and female division II basketball players during practice - Thigpen, L. K.; Green, J. M.; O'Neal, E. K. (The Journal of Strength and Conditioning Research, 2014)
Hydration affects multiple aspects of basketball performance, but few investigations have examined the hydration profiles of collegiate basketball players. We examined multiday prepractice hydration status of 11 male and 11 female NCAA (National Collegiate Athletic Association) Division II basketball players` sweat losses, fluid intake, and how accurately players estimated their sweat losses. Urine-specific gravity (USG) was spontaneously assessed before 2 practices. Sweat losses and fluid intakes were measured during a conditioning practice (CP) and sport-specific practice (SP). After practices, players filled 1,030 ml practice bottles to estimate their sweat losses. Urine-specific gravity between practices exhibited a moderate correlation (r = 0.54; p = 0.012) and were consistently high (17% of samples = USG >1.030) with no difference in mean USG between men (1.026 ± 0.004) and women (1.022 ± 0.008). Athletes' estimations of their sweat loss volumes between CP and the longer SP were strongly correlated (r = 0.88; p < 0.001). Estimation error was high (absolute error for both practices = 71 ± 52%) and error direction varied greatly within men. Women consistently underestimated sweat losses by 63 ± 28% and 65 ± 20% during CP and SP. Sweat losses during SP equaled 2,471 ± 495 ml and 1,910 ± 441 ml for men and women, respectively, but high practice fluid intake limited body mass losses to 1.1 ± 0.6% by the end of practice. It is plausible that hypohydration is related to poor conceptualization of sweat losses. Simulating the methodology of this study could help identify chronically hypohydrated athletes and be used to educate on between-practice fluid needs.